Impact of Fetal Versus Perinatal Hypoxia on Sex Differences in Childhood Outcomes: Developmental Timing Matters - Anastario, Michael (2011)
PURPOSE: To examine how the timing of hypoxic exposure results in specific childhood outcomes and whether there is a differential effect by sex. METHODS: A sample of 10,879 prospectively followed pregnancies was drawn from the Boston and Providence sites (New England-NE) of the National Collaborative Perinatal Project. Based on placental pathology, we developed and validated a measure of probable chronic fetal hypoxia (CHP) and contrasted the effects of acute perinatal hypoxia on age 7 emotional, behavioral, and cognitive outcomes. RESULTS: Perinatal hypoxia had a significant impact on multiple behavioral and cognitive outcomes in boys and girls by age 7, in contrast to probable CHP which had a differential effect on girls and boys such that there was decreased verbal IQ and increased inhibition in females alone. CONCLUSIONS: Findings underscore the importance of considering the timing of obstetric complications and offspring sex in investigations of the impact of fetal and perinatal hypoxia on offspring’s outcomes throughout the life course.